ICT implementation barriers and organizational issues in Islamic-based higher education institution: the case of Syarif Hidayatullah State Islamic University (UIN) Jakarta - Qomarul Huda, M; Hussin, Husnayati (2010)
Nowadays, most Higher Education Institutions(HEI) rely on Information and Communication Technology(ICT) for all aspects of their activities such as administration, teaching, learning and research services. Even though the adoption of ICT in higher education has been extensive since mid 1990s, it has failed to produce the radical changes in learning and teaching. While many studies have been conducted on ICT usage in higher education especially in the developed countries, similar studies in the context of Islamic-based higher education institution(IHEI) are scarce. IHEI are unique institutions because its mission and vision are based on Islamic teachings and values. While it is well recognized that ICT implementation is a complex process, planning its use in the context of IHEI posed a greater challenge due to the cultural factor and the negative attitude towards the technology. This paper presents the analysis of ICT implementation barriers and organizational issues at DIN Jakarta, as a case study of an Islamic-based higher education institution in Indonesia. The findings revealed that the barriers include aspects related to organizational constraints, technological constraints, IT management problems, individual and cultural factors. While most factors are common, the aspect of organizational culture factor that relates to its being a religious institution is unique to this HEI.